2023
DOI: 10.3390/biomedicines11041175
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound and Bone Health in Elderly People, a Systematic Review

Abstract: Reduced bone mineral density (BMD), osteoporosis, and their associated fractures are one of the main musculoskeletal disorders of the elderly. Quickness in diagnosis could prevent associated complications in these people. This study aimed to perform a systematic review (SR) to analyze and synthesize current research on whether a calcaneal quantitative ultrasound (QUS) can estimate BMD and predict fracture risk in elderly people compared to dual-energy x-ray absorptiometry (DXA), following the PRISMA guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…With regard to research methods, qualitative and quantitative research methods are divided, and most studies adopt qualitative research methods. In the quantitative studies, the web of science (WOS) database is analyzed by using advanced analysis tools [28] , e.g., CiteSpace software, HistCite software, Pajek software, etc. Accordingly, this paper attempts to analyze and discuss the relevant problems of medical AI research based on WOS publication data (2013-2023) and using CiteSpace, HistCite, and Pajek bibliometric and scientometric tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to research methods, qualitative and quantitative research methods are divided, and most studies adopt qualitative research methods. In the quantitative studies, the web of science (WOS) database is analyzed by using advanced analysis tools [28] , e.g., CiteSpace software, HistCite software, Pajek software, etc. Accordingly, this paper attempts to analyze and discuss the relevant problems of medical AI research based on WOS publication data (2013-2023) and using CiteSpace, HistCite, and Pajek bibliometric and scientometric tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Escobio-Prieto et al assessed the use of DEXA vs. calcaneal QUS in a systematic review to determine and analyze the use of the latter in terms of bone disease prevention and diagnosis. They concluded that the calcaneal QUS tool may be a promising method to evaluate BMD in elderly people, facilitating its prevention and diagnosis [7].…”
mentioning
confidence: 99%